Making women count : a history of the Women's Electoral Lobby - Sawer, Marian (UNSW Press, 2008)
"This is the first full-scale history of the Women's Electoral Lobby in Australia, which burst onto the scene of federal politics in 1972. It assesses WEL's significance as a policy actor and its attempts to shape public agenda, as well as the meaning of WEL for those involved and its impact on their lives. WEL is the women's organisation most often referred to in parliament and the media."--Provided by publisher